Determination of Flowering Dates and Pollen Properties of Some Pecan Nut Cultivars in Adana Ecological Conditions - Senay Karabıyık; Sinan Eti (Turkish Journal of Agriculture: Food Science and Technology)
The aim of this study is to determine the functionality period of pistillate and staminate flower types and the pollen viability and normally developed pollen rates with pollen production in staminate flowers of monoecious pecan nut cultivars in Adana ecological conditions. In the study, 11 pecan nut cultivars named as Coctaw, Comanche, Harris Super, Hastings, Ideal, Mahan, Royal, Shawnee, Texhan, Western and Wichita were used. Flowering periods of evaluated cultivars were determined as homogamous, protandrous, partially protandrous and partially protogynous. The flowering dates occur between 3rd-20th May in 2016 and 30th April-18th May in 2017. The pollen viability rates were found to be quite high in all cultivars, but in 2017 the rates were lower than 2016. The lowest pollen viability rates were obtained from Hastings in 2016 and 2017 (60.0% and 61.6%) respectively and the highest rates were in Shawnee (89.1%) at 2016 and in Mahan (87.7%) at 2017. Normally developed pollen rates were adequate for all cultivars and the rates were differed between 92.30% and 98.42% in 2016, and 90.20% 97.24% in 2017. The differences between cultivars in terms of pollen production were significantly important. The pollen number in one catkin was found between 3.512.382 and 11.097.407 at 2016 and 6.101.233 and 14.958.453 at 2017.